Data envelopment analysis models and software packages for academic purposes - Iliyasu, Abdullahi; Mohamed, Zainal Abidin; Terano, Rika (School of Graduate Studies, Universiti Putra Malaysia, 2015)
Data envelopment analysis (DEA) is a popular technique used in measuring the performance of an industry. DEA has wide applications in agriculture, manufacturing, health care, transportation, education, energy and environment, as well as banking and finance. However, many students and academicians are in dilemma in finding the appropriate software to execute a particular DEA model. In recent years, different DEA software packages have been developed by some universities and companies for both academic and commercial purposes. The software packages offered wide varieties of most recent DEA models that could be used in science and technology. Some of these software packages are free for academic users while others are commercialised. In this study, nine different DEA software packages were reviewed. Among them, only three are free for academic purposes while four have been commercialized. One of the former is still in the development stage, but expected to be available soon.